High-performance hydrolysis-resistant film-grade flame-retardant PC material and preparation method thereof

By mixing specially made flame retardant masterbatches with PC, toughening agent, anti-drip agent, antioxidant and lubricant in specific specific gravity, the problem of high flame retardancy requirements in the insulating film field of new energy vehicle battery is solved, and the preparation of high-performance hydrolysis-resistant film-grade flame retardant PC materials is achieved, reaching the V0 flame retardant level and taking into account environmental protection needs.

CN119552490APending Publication Date: 2025-03-04JINYOUNG XIAMEN ADVANCED MATERIALS TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411613548.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The prior art is difficult to meet the high flame retardancy requirements in the field of insulating films of new energy vehicle batteries. Traditional flame retardants have problems of toxicity, hydrolysis and flame retardant effects at the film level.

Method used

Using special flame retardant masterbatches, high-performance hydrolysis-resistant film-grade flame retardant PC materials are prepared by grafting PC, fluorosiloxane-containing GMA polymer, flame retardant and antioxidant in a specific mass ratio, and granulated by high mixer stirring and twin screw extruder.

Benefits of technology

It improves the flame retardant and hydrolysis resistance of PC materials, enhances the comprehensive mechanical properties of the material, and takes into account environmental protection needs, and can achieve V0 flame retardant level at the 0.5mm film level.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the technical field of high polymer materials, in particular to a high-performance hydrolysis-resistant film-grade flame-retardant PC material and a preparation method thereof. According to the high-performance hydrolysis-resistant film-grade flame-retardant PC material provided by the invention, the specially-made flame-retardant master batch is mixed with the PC, the flexibilizer, the anti-dripping agent, the antioxidant and the lubricant according to a specific proportion, and through the synergistic effect of the components, the flame retardance and hydrolysis resistance of the PC material are improved, meanwhile, the comprehensive mechanical property of the material is improved, the environmental protection requirement is met, and the high-performance hydrolysis-resistant film-grade flame-retardant PC material is suitable for industrial production. The flame-retardant grade of the film can reach V0 after the film is processed into the film with the thickness of 0.5 mm, and the film can be applied to the field of films with flame-retardant and hydrolysis-resistant requirements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a high-performance hydrolysis-resistant film-grade flame-retardant PC material and a preparation method thereof. Background Art

[0002] Polycarbonate (PC) resin is an engineering plastic with excellent comprehensive performance, with special toughness, heat resistance, transparency and flame retardancy, and a flame retardancy grade of V-2. It is widely used in electronic appliances, automobiles and other fields. Although PC resin itself has certain flame retardancy, it is difficult to meet the requirements in some fields with higher flame retardancy requirements, such as the insulation film of new energy vehicle batteries, which has a thickness of 0.1-0.75mm.

[0003] Although traditional flame retardants can improve the flame retardancy of PC, they are not applicable in the field of new energy films. Flame retardants are mainly divided into bromine flame retardants, sulfonate flame retardants, phosphorus flame retardants and silicon flame retardants according to the type of elements. Although bromine flame retardants can meet ROHS requirements, they will produce toxic and harmful gases during the combustion process. With the further tightening of environmental protection policies, their use is restricted; sulfonate flame retardants have a certain limit on their effective content, and it is difficult to achieve V0 flame retardancy below 1mm; phosphorus flame retardants have a great impact on toughness and heat resistance, and are easily hydrolyzed, which is not suitable for the field of new energy films; in addition, pure silicon flame retardants are also difficult to achieve V0 flame retardancy below 1mm.

[0004] Therefore, how to prepare a film-grade flame-retardant PC material is a technical problem that those skilled in the art need to solve urgently. Summary of the invention

[0005] In order to overcome the shortcomings and deficiencies in the prior art, the present invention provides a high-performance hydrolysis-resistant film-grade flame-retardant PC material and a preparation method thereof.

[0006] The high-performance hydrolysis-resistant film-grade flame-retardant PC material provided by the present invention comprises, by weight: PC78-93 copies; 5-20 parts of special flame retardant masterbatch; Toughener 0.5-3 parts; Anti-dripping agent 0.3-0.8 parts; Antioxidant 0.1-0.5 parts; Lubricant 0.1-0.5 parts; The special flame retardant masterbatch is prepared by compounding PC, fluorinated silicone grafted GMA polymer, flame retardant and antioxidant in a mass ratio of 80-90:10-20:2-4:0.1-0.5.

[0007] On the basis of the above technical solution, further, the fluorine-containing siloxane grafted GMA polymer is a polymer containing silicone in the main chain and fluorine in the side chain, and grafted with GMA.

[0008] By adopting the above technical scheme, the main chain of the fluorinated siloxane grafted GMA polymer contains organic silicon, which provides the polymer with a larger bond angle and free volume, thereby improving the flexibility, high temperature resistance and hydrolysis resistance of the PC material; its side chain contains organic fluorine, which can form a layer of fluoride film with flame retardant effect when encountering flame to inhibit or slow down the spread of combustion, thereby improving the flame retardancy of the PC material; GMA also has acrylate double bonds and epoxy groups, which can react with the terminal hydroxyl groups of PC, thereby improving the hydrolysis resistance of the PC material.

[0009] On the basis of the above technical solution, further, the preparation method of the special flame retardant masterbatch is: A certain weight of PC, fluorinated silicone grafted GMA polymer, flame retardant and antioxidant are placed in a high-speed mixer and stirred for 3-10 minutes to obtain a mixture; the mixture is then granulated by a twin-screw extruder at 250-280°C and a rotation speed of 200-600 rpm to obtain a special flame retardant masterbatch.

[0010] On the basis of the above technical solution, further, the melt flow rate of the PC is 3-8 g / 10 min under the condition of 300° C. / 1.2 kg.

[0011] The purpose of adopting the above technical scheme is that when the melt flow rate of PC is too high, it will affect the mechanical properties, hydrolysis resistance and flame retardancy of the material; when the melt flow rate of PC is too low, it will cause processing difficulties. Therefore, using PC with a melt flow rate of 3-8g / 10min can effectively balance the processing performance of the material and the mechanical properties, hydrolysis resistance and flame retardancy of the finished product.

[0012] On the basis of the above technical solution, further, the antioxidant is a hindered phenol and / or a phosphite compound.

[0013] Preferably, the antioxidant is a mixture of octadecyl β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and tris(2,4-di-tert-butylphenyl) phosphite in a mass ratio of 1:1.

[0014] On the basis of the above technical solution, further, the toughening agent is butadiene-styrene copolymer grafted with polymethyl methacrylate.

[0015] The above technical scheme is adopted, and butadiene-styrene copolymer grafted polymethyl methacrylate is used as a toughening agent. Butadiene-styrene copolymer grafted polymethyl methacrylate is a terpolymer formed by polymerization of three monomers: butadiene, styrene and methyl methacrylate. Therefore, it has a two-phase structure at room temperature - a rubber continuous phase of polybutadiene and a resin micro-region of polystyrene. This structure enables butadiene-styrene copolymer grafted polymethyl methacrylate to have good elasticity and low temperature resistance, thereby improving the toughness of the PC material.

[0016] On the basis of the above technical solution, further, the lubricant is calcium stearate and / or polyethylene wax.

[0017] Preferably, the lubricant is pentaerythritol stearate PETS.

[0018] On the basis of the above technical solution, further, the anti-dripping agent is polytetrafluoroethylene dispersed in an AS matrix coating.

[0019] On the basis of the above technical solution, further, the flame retardant is a sulfonate flame retardant.

[0020] Specifically, the flame retardant is Airchem F535 flame retardant.

[0021] The present invention also provides a method for preparing a high-performance hydrolysis-resistant film-grade flame-retardant PC material, comprising the following steps: After weighing PC, special flame retardant masterbatch, toughening agent, anti-dripping agent, antioxidant and lubricant according to weight ratio, put them into a high-speed mixer and stir for 3-10 minutes to obtain a mixture; then the mixture is passed through a twin-screw extruder at 250-280°C and a rotation speed of 200-600 rpm for melt blending and extrusion, cooled, pelletized, and the obtained particles are dried.

[0022] Compared with the prior art, the high-performance hydrolysis-resistant film-grade flame-retardant PC material provided by the present invention improves the flame retardancy and hydrolysis resistance of the PC material through the synergistic effect between the components by mixing a special flame retardant masterbatch with PC, a toughening agent, an anti-dripping agent, an antioxidant and a lubricant in a specific proportion, and at the same time improves the comprehensive mechanical properties of the material and takes environmental protection needs into account. After being processed into a 0.5 mm film, its flame retardancy level can reach V0 level. DETAILED DESCRIPTION

[0023] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] The present invention provides the following embodiments and comparative examples: The formula of the special flame retardant masterbatch 1-3 and the common flame retardant masterbatch provided by the present invention is as follows in Table 1: Table 1 Flame retardant masterbatch ratio (unit: kg)

[0025] Example 1 A method for preparing a high-performance hydrolysis-resistant film-grade flame-retardant PC material comprises the following steps: S1. By weight, 88 parts of PC, 10 parts of special flame retardant masterbatch, 1 part of toughening agent, 2 parts of anti-dripping agent, 0.5 parts of antioxidant, and 0.3 parts of lubricant are mixed evenly; S2. Add the above mixture into a high-speed mixer and stir for 3-10 minutes to obtain a mixture; then pass the mixture through a twin-screw extruder at 250-280° C. and a rotation speed of 200-600 rpm for melt blending, extrusion, cooling, pelletizing, and drying the obtained particles for standby use.

[0026] Example 2 The PC in Example 1 is replaced by 78 parts, the special flame retardant masterbatch 1 is replaced by 20 parts, and the remaining operations and steps are the same as in Example 1.

[0027] Example 3 The special flame retardant masterbatch 1 in Example 1 is replaced by the special flame retardant masterbatch 2, and the remaining operations and steps are the same as those in Example 1.

[0028] Example 4 The special flame retardant masterbatch 1 in Example 2 is replaced by the special flame retardant masterbatch 2, and the remaining operations and steps are the same as those in Example 2.

[0029] Example 5 The PC in Example 1 is replaced by 93 parts, and the 88 parts of the special flame retardant masterbatch 1 is replaced by 5 parts of the special flame retardant masterbatch 3. The remaining operations and steps are the same as those in Example 1.

[0030] Example 6 The special flame retardant masterbatch 1 in Example 1 is replaced by the special flame retardant masterbatch 3, and the remaining operations and steps are the same as those in Example 1.

[0031] Comparative Example 1 By weight, 98 parts of PC, 2 parts of toughening agent, 0.5 parts of anti-dripping agent, 0.3 parts of antioxidant and 0.3 parts of lubricant are mixed evenly. The preparation process S2 is the same as that of Example 1.

[0032] Comparative Example 2 By weight, 88 parts of PC, 10 parts of common flame retardant masterbatch, 2 parts of toughening agent, 0.5 parts of anti-dripping agent, 0.3 parts of antioxidant and 0.3 parts of lubricant are mixed evenly, and the preparation process S2 is the same as that of Example 1.

[0033] The flame retardant masterbatch of Comparative Example 2 is a common flame retardant masterbatch, wherein the common flame retardant masterbatch is compounded with 90 parts of PC, 3 parts of flame retardant and 0.3 parts of antioxidant.

[0034] The difference between the common flame retardant masterbatch and the special flame retardant masterbatch is that the fluorinated silicone grafted GMA is not added to the common flame retardant masterbatch.

[0035] The flame retardant PC material formulas of Examples 1-6 and Comparative Examples 1-2 are shown in Table 2: Table 2 Flame retardant PC material formula (unit: kg)

[0036] The flame retardant PC materials prepared in Comparative Examples 1-2 and Examples 1-6 were tested for performance as follows. The test results are shown in Table 3: After the particles are fully dried, the specimens and plates are prepared using an injection molding machine and tested after being left for 24 hours.

[0037] Among them: The test methods for tensile strength and elongation at break refer to: GB / T 1040-2018, test speed 50mm / min; The test method for simply supported beam notched impact strength is based on: GB / T 1043.1-2008, A-type notch; Combustion performance test method reference: GB / T 2408-2008, 0.5mm, vertical method; Hydrolysis resistance test method: Place the test specimen in a high and low temperature aging box, at 85°C and 85% humidity, and perform performance test after aging for 1000 hours.

[0038] Table 3

[0039] As can be seen from Table 3, compared with Comparative Example 1 without adding flame retardant masterbatch and Comparative Example 2 adding ordinary flame retardant masterbatch, the flame retardant effects of Examples 1-6 after being processed into 0.5 mm films all reached V0 level; after 1000H wet heat aging, the elongation at break and the simply supported beam notched impact strength of Examples 1-6 were significantly higher than those of the comparative examples, and the flame retardant effects of Examples 2, 3 and 6 still maintained V0 level, indicating that the hydrolysis resistance of the special flame retardant masterbatch provided by the present invention is significantly improved.

[0040] In summary, the high-performance hydrolysis-resistant film-grade flame-retardant PC material provided by the present invention is obtained by mixing a special flame-retardant masterbatch with PC, a toughening agent, an anti-dripping agent, an antioxidant and a lubricant in a specific proportion. Through the synergistic effect between the components, the flame retardant and hydrolysis resistance of the PC material are improved, while the comprehensive mechanical properties of the material are improved and environmental protection needs are taken into account. The material can be applied to the film field with flame retardancy and hydrolysis resistance requirements.

[0041] Although the terms such as PC, special flame retardant masterbatch, film grade, etc. are used more frequently in this article, the possibility of using other terms is not excluded. These terms are used only to more conveniently describe and explain the essence of the present invention; interpreting them as any additional restrictions is contrary to the spirit of the present invention.

[0042] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A high-performance hydrolysis-resistant film-grade flame-retardant PC material, characterized by: The components include, by weight: PC78-93 copies; 5-20 parts of special flame retardant masterbatch; Toughener 0.5-3 parts; Anti-dripping agent 0.3-0.8 parts; Antioxidant 0.1-0.5 parts; Lubricant 0.1-0.5 parts; The special flame retardant masterbatch is prepared by compounding PC, fluorinated silicone grafted GMA polymer, flame retardant and antioxidant in a mass ratio of 80-90:10-20:2-4:0.1-0.

5.

2. The high-performance hydrolysis-resistant film-grade flame-retardant PC material according to claim 1, characterized in that: The fluorine-containing siloxane grafted GMA polymer is a polymer containing silicone in the main chain and fluorine in the side chain, and grafted with GMA.

3. The high-performance hydrolysis-resistant film-grade flame-retardant PC material according to claim 1, characterized in that: The preparation method of the special flame retardant masterbatch is: A certain weight of PC, fluorinated silicone grafted GMA polymer, flame retardant and antioxidant are placed in a high-speed mixer and stirred for 3-10 minutes to obtain a mixture; the mixture is then granulated by a twin-screw extruder at 250-280°C and a rotation speed of 200-600 rpm to obtain a special flame retardant masterbatch.

4. The high-performance hydrolysis-resistant film-grade flame-retardant PC material according to claim 1, characterized in that: The melt flow rate of the PC is 3-8 g / 10 min under the conditions of 300° C. / 1.2 kg.

5. The high-performance hydrolysis-resistant film-grade flame-retardant PC material according to claim 1, characterized in that: The antioxidant is a hindered phenol and / or a phosphite compound.

6. The high-performance hydrolysis-resistant film-grade flame-retardant PC material according to claim 1, characterized in that: The toughening agent is butadiene-styrene copolymer grafted with polymethyl methacrylate.

7. The high-performance hydrolysis-resistant film-grade flame-retardant PC material according to claim 1, characterized in that: The lubricant is calcium stearate and / or polyethylene wax.

8. The high-performance hydrolysis-resistant film-grade flame-retardant PC material according to claim 1, characterized in that: The anti-dripping agent is polytetrafluoroethylene dispersed in an AS matrix.

9. The high-performance hydrolysis-resistant film-grade flame-retardant PC material according to claim 2, characterized in that: The flame retardant is a sulfonate flame retardant.

10. A method for preparing a high-performance hydrolysis-resistant film-grade flame-retardant PC material according to any one of claims 1 to 9, characterized in that: The steps include: After weighing PC, special flame retardant masterbatch, toughening agent, anti-dripping agent, antioxidant and lubricant according to weight ratio, put them into a high-speed mixer and stir for 3-10 minutes to obtain a mixture; then the mixture is passed through a twin-screw extruder at 250-280°C and a rotation speed of 200-600 rpm for melt blending and extrusion, cooled, pelletized, and the obtained particles are dried.